2021
DOI: 10.5853/jos.2021.00626
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of GV1001 in Animal Stroke Model and Neural Cells Subject to Oxygen-Glucose Deprivation/Reperfusion Injury

Abstract: Background and Purpose Previous studies have revealed the diverse neuroprotective effects of GV1001. In this study, we investigated the effects of GV1001 on focal cerebral ischemia-reperfusion injury (IRI) in rats and oxygen-glucose deprivation/reoxygenation (OGD/R)-induced injury in neural stem cells (NSCs) and cortical neurons. Methods Focal cerebral IRI was induced by transient middle cerebral artery occlusion (MCAO). Brain diffusion-weighted imaging (DWI) was performed 2 hours after occlusion, and a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It was suggested that TERT protects neurons from apoptosis induced by various stresses including cerebral hypoxia-ischemia by increasing the expression rate of Bcl-2/Bax and decreasing ROS production [123] . Zhang et al verified that rapid nuclear stimulation of the cerebellum could achieve neuroprotection by upregulating the expression of TERT, and then increasing telomerase activity, in adult male SD rats [126] . Kwon et al demonstrated the neuroprotective effect of GV1001 against focal cerebral ischemia-reperfusion injury and OGD/reoxygenation-induced injury in NSCs and cortical neurons in rats [127] .…”
Section: Telomeres and Telomerase And Hypoxic-ischemic Encephalopathymentioning
confidence: 99%
“…It was suggested that TERT protects neurons from apoptosis induced by various stresses including cerebral hypoxia-ischemia by increasing the expression rate of Bcl-2/Bax and decreasing ROS production [123] . Zhang et al verified that rapid nuclear stimulation of the cerebellum could achieve neuroprotection by upregulating the expression of TERT, and then increasing telomerase activity, in adult male SD rats [126] . Kwon et al demonstrated the neuroprotective effect of GV1001 against focal cerebral ischemia-reperfusion injury and OGD/reoxygenation-induced injury in NSCs and cortical neurons in rats [127] .…”
Section: Telomeres and Telomerase And Hypoxic-ischemic Encephalopathymentioning
confidence: 99%
“…For example, GV1001, a peptide vaccine derived from the active site sequence of hTERT, initially developed as an anti-cancer agent, was later found to also have anti-aging effects. In particular, it was able to relieve the effects of Aβ and oxygen–glucose deprivation/reoxygenation-mediated oxidative stress by inhibiting the production of ROS [ 119 , 120 ]. GV1001 also promoted neuronal regeneration by restoring the PI3k-mTOR pathway, which is involved in cell survival and proliferation [ 121 ].…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…GV1001 is a small peptide containing 16 amino acids that mimics a fragment of the active catalytic site of human telomerase reverse transcriptase (hTERT). GV1001 has been previously reported to have various biological functions, including antioxidant, antiinflammatory, anti-aging, anti-apoptotic, and mitochondrial stabilisation effects, mimicking the extratelomeric function of hTERT [14][15][16]. Based on these beneficial effects, GV1001 was applied in a phase II clinical trial for the treatment of moderate to severe AD, and the results showed that a significant improvement in cognitive function was observed in patients with moderate to severe AD treated with GV1001, at weeks 12 and 24 [17].…”
Section: Introductionmentioning
confidence: 99%